A novel connectivity and coverage algorithm based on shortest path for wireless sensor networks. (October 2018) - Sun, Geng; Liu, Yanheng; Li, Han; Wang, Aimin; Liang, Shuang; Zhang, Ying
Abstract: A novel shortest path connectivity and coverage algorithm (SPCCA) for wireless sensor networks is proposed to reduce the energy consumption and to extend the network lifetime. The main procedure of SPCCA is as follows: first, each node determines whether it is the redundant node. Then, the redundant nodes enter into the ready-to-sleep mode through the node selection method and the sleepless nodes enter into the active mode. In this way, the blind spot can be avoided and the energy balance can be guaranteed. Finally, the redundant nodes on the shortest path are woken up in order to guarantee the connectivity of the network. Simulation results show that the number of working nodes of SPCCA is stable and they do not increase with the number of the deployed nodes. Moreover, SPCCA has better performance than most homogeneous algorithms in terms of the network coverage, connectivity, connection cost and network lifetime.